STRATEGI PEMBIMBING ROHANI UNTUK MENGATASI KECEMASAN PASIEN KANKER PAYUDARA DI RS. KANKER DHARMAIS JAKARTA - ABDUL AZIS; RIZKY NOVEBRIANSYAH; DWI PUTRI JULIA (TASÂMUH, 2021)
An individual living in the world is bound to undergo three essential states: health, illness, or death. Life itself is always coloured by contradictory things, which alternately fill life without ever being empty. Health and illness are colours that are always inherent in individuals as long as they are alive. Individuals who are in a state of illness in addition to complaining of physical suffering are usually accompanied by disturbances / mental shocks with mild symptoms such as stress to a more severe level. After a diagnosis of illness, anxiety is a common response. Patients can be confused about the potential changes that occur. Anxiety can affect health function. Health conditions can become worse if a person has excessive anxiety. This study aims to determine and analyze the strategy of Islamic spiritual mentors for patients to overcome anxiety and also to find out what are the obstacles to spiritual mentors in overcoming the anxiety of breast cancer patients in hospitals. Dharmais Cancer Jakarta. This study uses a qualitative approach with phenomenological methods. The research subjects consisted of 7 informants, consisting of 3 breast cancer patients, 3 significant others, 1 spiritual guide at the hospital. Dharmais Cancer Jakarta. This study uses 3 data collection techniques, namely interviews, observation and documentation. This study uses 3 data analysis techniques, namely: Data Reduction, Data Presentation, and Conclusion Drawing. The results of this study become a real picture that an appropriate spiritual guidance strategy is needed at Dharmais Cancer Hospital, which will have an impact on reducing the anxiety felt by the patients. The results of the study are expected to make the instructors, especially students of Islamic guidance and counselling, better understand the needs of the patients in solving their psychological problems, so that the patients have the spirit of life with reduced anxiety in themselves.